1998
DOI: 10.1016/s0029-7844(97)00654-6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinical and Ultrasonic Estimation of Fetal Weight

Abstract: Clinical estimation of birth weight in early labor is as accurate as routine ultrasonic estimation obtained in the preceding week. In the lower range of birth weight (less than 2500 g), ultrasonic estimation is more accurate; in the 2500-4000 g range, clinical estimation is more accurate. In the higher range of birth weight (greater than 4000 g), both methods have similar accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
97
2
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 14 publications
16
97
2
3
Order By: Relevance
“…There are several methods of estimating intrauterine fetal weight like tactile assessment of the fetal size, risk factors assessment, maternal self estimation and ultrasonography. 1,2 The advantage of the ultrasonographic technique is that it relies on linear and/or planar measurement of in-utero fetal dimensions that can be defined objectively and are reproducible. 3 Multiple formulae have been developed for the estimation of birth weight using ultrasound measurement; using abdominal circumference (AC) alone, AC and biparietal diameter (BPD) and AC, BPD and femur length.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods of estimating intrauterine fetal weight like tactile assessment of the fetal size, risk factors assessment, maternal self estimation and ultrasonography. 1,2 The advantage of the ultrasonographic technique is that it relies on linear and/or planar measurement of in-utero fetal dimensions that can be defined objectively and are reproducible. 3 Multiple formulae have been developed for the estimation of birth weight using ultrasound measurement; using abdominal circumference (AC) alone, AC and biparietal diameter (BPD) and AC, BPD and femur length.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, management of diabetic pregnancy, vaginal birth after a previous caesarean section, and intrapartum management of fetuses presenting by the breech will be greatly influenced by estimated fetal weight. 8,9 During the initial era or before the birth of science fetal weight estimation was more a kind guess work. The cardinal importance of knowledge of the size and shape of the fetal head in order to understand the mechanism of labor was first recognized by Smellie (1752) who also pointed out that it is the biparietal diameter which passes through the narrowest part of the pelvic brim.…”
Section: Introductionmentioning
confidence: 99%
“…60 Moreover, studies comparing clinical and US measurements found neither method superior, US proving more accurate only in the low birth weight range. 61 A recent study also showed that the positive predictive value of US in assessing birth weights above the 95th percentile in women with varying degrees of glucose intolerance is only 50%. 62 In another recent study, Pates et al 63 found that US estimates of fetal weight of 4000 g or more, based on fetal abdominal circumference, biparietal diameter, head circumference and femur length, within a week of delivery and a higher than normal amniotic fluid index in combination with clinical risk factors (maternal parity, BMI and diabetes) improved the prediction of macrosomia from 61% to 71%.…”
Section: Obstetric Managementmentioning
confidence: 99%